Untersuchung und Optimierung der Fahrkomfort- und Fahrdynamikeigenschaften von Radladern unter Berücksichtigung der prozessspezifischen Randbedingungen - Bös, Manuel (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2015)
The objective of this work is to provide an efficient solution to analyze and optimize global dynamic vehicle behavior of wheel loaders in the areas of vibration comfort, vehicle dynamics and tipping safety. To quantify the vehicle’s behavior several virtual tests and maneuvers are automatically performed by a full-vehicle simulation model of the machine. The results are then analyzed and combined to provide objective measures representing the global dynamic vehicle behavior.